Keruntuhan Konteks pada Konten Edukasi Kesehatan Anak di Media Sosial - Yuliana, Gati Dwi; Virgiansyah, Yusril; Adha, Aiskha Atthaya (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study examines the context collapse that occurs in digital health campaigns that intersect with the media literacy of social media users. The reality of context collapse is observed in the interaction of the Insta story question and answer column archived in the Instagram account highlights of health workers. Interviews were conducted with key informants who are media literacy practitioners, child development therapists, and communication teachers. The results of the study show that the context on social media can be collapsed by both the uploader and the content user. Both are communicators who take turns exchanging messages in a virtual face-to-face interaction. Social media followers are random audiences, so their behavior towards an upload, including child health education content, still carries the risk of triggering a reactive response even from a health professional. The key to navigating context collapse on social media is first, refraining from certain behaviors on social media, second, building boundaries for certain activities on social media. These two steps are taken to avoid unnecessary, inappropriate reactions that can obscure or even thwart the initial purpose of communication designed on social media.